2017
DOI: 10.2217/fon-2016-0468
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Site and Anti-EGFR Monoclonal Antibody Benefit in Metastatic Colorectal Cancer: A Meta-Analysis

Abstract: This meta-analysis demonstrated that LCC had markedly superior anti-EGFR mAb treatment benefit compared with RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…This possibly explains the much better predictive performance of EGFR-HS detected in metastases. A multivariate analysis indicated that the EGFR protein expression of both the primary as well as the metastatic tissues is not an independent predictor of cetuximab efficacy unlike sidedness, confirming previous reports [17,18]. However, sidedness is not an EGFR-independent factor since it was shown recently that there is a close connection between EGFR protein expression and sidedness [11,19]: the poorly responding right-sided tumors express EGFR at significantly higher levels as compared to those left-sided [11].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This possibly explains the much better predictive performance of EGFR-HS detected in metastases. A multivariate analysis indicated that the EGFR protein expression of both the primary as well as the metastatic tissues is not an independent predictor of cetuximab efficacy unlike sidedness, confirming previous reports [17,18]. However, sidedness is not an EGFR-independent factor since it was shown recently that there is a close connection between EGFR protein expression and sidedness [11,19]: the poorly responding right-sided tumors express EGFR at significantly higher levels as compared to those left-sided [11].…”
Section: Discussionsupporting
confidence: 78%
“…Fortunately, strong negative predictors of the efficacy of anti-EGFR antibody therapies have been discovered: first KRAS exon2-, then rare KRAS-and NRAS mutations, and more recently BRAF mutations, the use of which improved patient selection for therapy [14][15][16]. Furthermore, it was also recently discovered that left-sided colorectal cancers respond significantly better to anti-EGFR therapies than do right-sided colorectal cancers [17,18]. Data also demonstrated that there is a difference in EGFR protein expression between left-and right-sided colorectal cancers that is independent from the RAS mutation statuses [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an increasing number of studies reported that colon cancer can be divided according to distal and proximal colon cancer (2628). Our research did not detect a difference between colon cancer in the left and right colons.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 37 published a meta-analysis of primary tumour site and anti-egfr mAb benefit in mcrc. The analysis of the prognostic value of ptl included eleven studies, but the analysis of the predictive effect was limited to just two randomized controlled trials (crystal and ncic co.17).…”
Section: Meta-analyses Of the Effect Of Ptlmentioning
confidence: 99%
“…In addition, although most trials defined lcc as beginning at the splenic flexure, the calgb 80405 and Australasian Gastrointestinal Trials Group max trials excluded the transverse colon in their analysis. Furthermore, there is evidence to show that, even within rcc and lcc, significant heterogeneity is evident with respect to molecular characteristics 34,37 , such that classification by side could be oversimplifying a more complex interaction between tumour and treatment. Finally, to date, no data are available about the effect of ptl in the context of triplet therapy (that is, folfoxiri) combined with either bevacizumab or an efgr mAb.…”
Section: Limitationsmentioning
confidence: 99%